A research study on the effectiveness of practicum course offered by the university of the Philippines in the Visayas college of management in preparing graduates for the actual work - Mercurio, Michelle M.; Pingoy, Mary Jane S.; Selibio, Annabelle S.; Tanalan, Hazel P.
Practicum courses have been a part of UPV-CM curriculum for a long time. Students are given the chance to work in various agencies in order to prepare themselves for actual employment after graduation. This study aims to assess the relevance and effectiveness of practicum courses. Another is to determine whether practicum helped UPV-CM graduates in their actual work. This study is conducted in Iloilo City with BS Management student of UPV of the years 1997-1999 as respondents. With the data gathered, the researchers analyzed them using the percentage system. Based on the results and findings, practicum courses are effective in preparing the graduates for actual employment. These courses offer students training as well as other benefits, which not only help them n looking for a job but also in performing in their actual jobs.